Pengaruh Perebusan Dengan Abu Sekam Dan Waktu Perendaman Air Terhadap Kadar Hcn Pada Buah Mangove Avicennia marina - Kurniawan, Ade; Wulandari, Sri Yulina; Supriyantini, Endang (977-2407769)
The potential of mangove fruit as a food source has not been known yet. Mangove is a potential material to be used as a food substitute, one of which is the process of making flour. One part of the Mangove is used for the manufacture of flour is the fruit of mangove A.marina. Toxins such as HCN in fruit may cause constraint in food processing, so it needs to be removed. The ways that can be done by immersion and boiling them with rice husk ash. Rice husk ash is material that is expected to absorb HCN as toxin in fruit. This research used Completely Randomized Design (CRD) factorial pattern consisting of two factors treatments with three replicates by 6 hours immersion time (4, 8 and 12 replications) and ash contents (5, 10, 15% W). Data were analyzed by two-way ANOVA using SPSS. The results showed that treatment with several concentrations of ash boiling and long water immersion to give a significant influence on levels of HCN A.marina mangove fruit flour. Treatment with boiling 15% ash content and 6 hours of water immersion to 12 replications provides the best results of the HCN content of fruit and flour mangove mangove A.marina